THE COMPARATIVE ANALYSIS OF VILLAGE FINANCIAL MANAGEMENT - Maya Yusnita; Wenni Anggita (AFEBI Management and Business Review, 2018)
West Bangka was the only regency in Bangka Belitung Province that received a Fair Without Exception (WTP) in 2013-2014. Different with the East Belitung which has never received a WTP, even in 2014 East Belitung received Unqualified Opinion (TW). This study aims to analyze and compare village financial management and its level of suitability with The Minister Regulation Number 113 Year 2014. Qualitative analysis used to identify the constraints on village financial management, analysis of quantitative using Independent Sample t Test. The object of this research are 26 villages in West Bangka and East Belitung. The results of this study showed that the obstacles of financial administration was caused by lack of understanding and guidance regarding the tasks, principal and functions of village apparatus. Reporting and financial accountability of the village is in accordance with the applicable rules, but there are 3 villages (11.54%) that have not been in accordance with The Minister Regulation Number 113 Year 2014. The results of descriptive statistics, there are differences in reporting and accountability of village finance. However, there is no difference regarding administration of village revenues, expenditures and financing in West Bangka and East Belitung.Keywords: Administration, Accountability, Village Financial Management